The 2016 U.S. Presidential Election and Transition Events: A Social Media Volume and Sentiment Analysis. Issue 3 (27th May 2019) - Boatwright, Brandon; Mazer, Joseph P; Beach, Sarah
ABSTRACT: The present study examines social media behavior as indicative of basking in reflected glory (BIRGing), the psychological process of associating with the successes of others, and cutting off reflected failure (CORFing), disassociating with the failure of others, during the 2016 presidential election, inauguration events, and subsequent worldwide Women's March. The study harvested 10, 973, 629 tweets in the days leading up to and following these events. The results indicate the presence of BIRGing and CORFing processes that were likely accelerated due to the election's outcome. While BIRG was uncovered during the election and inauguration, opponents were basking in reflected failure (BIRF) during the Women's March by protesting the inauguration as a form of resistance. We discuss the theoretical implications and areas for future research.